Signs of Social Class: The Experience of Economic Inequality in Everyday Life - Kraus, Michael W.; Park, Jun Won; Tan, Jacinth J. X. (Perspectives on psychological science, 2017)
By some accounts, global economic inequality is at its highest point on record. The pernicious effects of this broad societal trend are striking: Rising inequality is linked to poorer health and well-being across countries, continents, and cultures. The economic and psychological forces that perpetuate inequality continue to be studied, and in this theoretical review, we examine the role of daily experiences of economic inequality—the communication of social class signals between interaction partners—in this process. We theorize that social class signals activate social comparison processes that strengthen group boundaries between the haves and have nots in society. In particular, we argue that class signals are a frequent, rapid, and accurate component of person perception, and we provide new data and analyses demonstrating the accuracy of class signaling in 60-s interactions, Facebook photographs, and isolated recordings of brief speech. We suggest that barriers to the reduction of economic inequality in society arise directly from this class signaling process through the augmentation of class boundaries and the elicitation of beliefs and behaviors that favor the economic status quo.